Pengaruh Iradiasi Sinar Gamma dan Konsentrasi Kitosan terhadap Pembentukan Hidrogel Polivinil Alkohol-Kitosan - Zuhelmi Aziz; Gatot Trimulyadi; Trivena Fithriany A (JURNAL ILMU KEFARMASIAN INDONESIA, 2005)
Chitosan is one of the product from the shrimp disposal. Its medicinal and pharmaceutics application are now developed by pharmaceutical industries, i.e as bioplastics and hydrogel. A research about the effect of gamma radiation and chitosan as a raw material for production of polyvinilalcohol has been carried out. PVA-chitosan hydrogel was made from a mixture of composition of 80% PVA in 10% solution and 20% of chitosan in 0, 1, 2 ,and 3% solution respectively. The mixture was heated in oven at 80°C for two hours and then irradiated with 0, 15, 25, and 35 kGy gamma radiation. The physical characteristic of the gel was determined, e.g. colour, swelling degree and gel fraction. The colour of hydrogel more yellow darker to raising of chitosan concentration and radiation dosage. Swelling degree PVA-chitosan hydrogel increased meanwhile chitosan concentration and radiation dosage decreased. In absolute ethanol medium (96%) PVA-chitosan hydrogel was deswelling. The swelling degree PVAchitosan hydrogel decreased with increased gel fraction.